Pengaruh eko-enzim terhadap hasil dan mutu benih kedelai (Glycine max L.) - Swari, Elly Indra; Jasminarni, Jasminarni; Pebrianti, Herni Dwinta; Gusniwati, Gusniwati (Proceedings Academic Universitas Jambi, 2025)
This study aimed to examine the effect of eco-enzyme application on the growth, yield, and seed quality of soybean (Glycine max L.), as well as to determine the optimal concentration for promoting optimal growth. The research was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi, using a one-factor randomized complete block design (RCBD) consisting of five eco-enzyme concentration treatments (P0: 0 ml/L, P1: 10 ml/L, P2: 20 ml/L, P3: 7 ml/L + 3 ml/L foliar spray, P4: 14 ml/L + 6 ml/L foliar spray) with five replications. The results showed that eco-enzyme application had a significant effect on plant height, stem diameter, number of branches, and flowering time. Treatment P3 yielded the best results, with a plant height of 58.1 cm, stem diameter of 4.73 mm, and accelerated flowering time to 29.8 days compared to the control. Meanwhile, the highest number of branches was observed in treatment P4, with an average of 4.97 branches per plant. These findings demonstrate that eco-enzyme can function as an environmentally friendly organic biostimulant to support the enhancement of growth and seed quality in soybean.